2021
DOI: 10.1111/jph.12982
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. syringae as the new causal agent of cabbage leaf blight

Abstract: Cabbage with excellent source of vitamins, antioxidants and minerals, is among the most popular vegetables worldwide. In 2016, during our surveys of cabbage diseases in the Mazandaran province, Iran, symptoms of blight and detaching of leaves, water soaking, browning and decline were observed on the mature plants of cabbage (Brassica oleracea var. capitata). Bacterial isolation from the infected plants was performed using conventional microbiological methods. The isolated strains were identified through amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…All bacterial isolates belonged to Pss, previously reported as the causal agent of bacterial canker of many plants, including stone fruits, pear, quince, almond, olive, rose, malva and pelargonium, or causing red streak of sugarcane, blast of mandarin and leaf blight of wheat, rice, oat, barley and cabbage from different areas of Iran (Bahar et al, 1982;Banapour et al, 1990;Rahimian, 1995;Najafi Pour and Taghavi, 2011;Aeini and Khodakaramian, 2018;Khezri and Mohammadi, 2018;Vasebi et al, 2019;Basavand et al, 2021). Genomic fingerprinting analyses, including REP-, BOX-and IS50-PCR showed some levels of variability among the Pseudomonas strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All bacterial isolates belonged to Pss, previously reported as the causal agent of bacterial canker of many plants, including stone fruits, pear, quince, almond, olive, rose, malva and pelargonium, or causing red streak of sugarcane, blast of mandarin and leaf blight of wheat, rice, oat, barley and cabbage from different areas of Iran (Bahar et al, 1982;Banapour et al, 1990;Rahimian, 1995;Najafi Pour and Taghavi, 2011;Aeini and Khodakaramian, 2018;Khezri and Mohammadi, 2018;Vasebi et al, 2019;Basavand et al, 2021). Genomic fingerprinting analyses, including REP-, BOX-and IS50-PCR showed some levels of variability among the Pseudomonas strains.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, Pss strains were isolated and characterized as causal agents of bacterial canker of stone fruit hosts (cherry, peach, apricot), almond, olive, rose, mallow, pelargonium, pear, and quince, red streak of sugarcane, blast of mandarin, and leaf blight of wheat, rice, oat, barley, and cabbage, from different areas (Bahar et al, 1982;Banapour et al, 1990;Rahimian, 1995;Najafi Pour and Taghavi, 2011;Aeini and Khodakaramian, 2018;Khezri and Mohammadi, 2018;Vasebi et al, 2019;Basavand et al, 2021). Japanese quince trees showing sunken brown cankers were observed in the Sari county during the 2016 growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of the 16S rRNA gene is considered as a standard and simple method for the description of bacterial taxa (Basavand et al 2021b). The analysis of 16S rRNA sequence showed that strain P1 was 99% similar to A. radiobacter, which is in agreement with the results of the biochemical and physiological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Dark brown, water soaked, angular to irregular spots on fruit and leaves were observed in the spring of 2016 in two pomegranate orchards in Behshahr county, Mazandaran province, Iran. Yellow bacterial colonies were consistently isolated on nutrient agar from infected fruit and leaves (Basavand et al 2021). All five strains were characterized as gram negative, oxidase negative, catalase positive, anaerobic, and geranium (Pelargonium × hortorum) hypersensitivity positive (HR).…”
mentioning
confidence: 99%